The effect of 8 weeks of plyometric training on cortisol and DHEA levels in male badminton players - Khodami, A.; Nikseresht, A.; Khoshnam, E. (European Journal of Experimental Biology, 2014)
The portion of anabolic to catabolic hormones concentration is one of the most important physiological factors of exercise effectiveness and is one of overtraining symptoms. The purpose of the present study was to investigate the effect of 8 weeks of plyometric training on levels of Cortisol, DHEA and DHEA/C ratio in male badminton players. Subjects were 20 Badminton Players (age 15-18) who participated is the study voluntarily and were randomly assigned in plyometric (n=10) and control (n=10) groups. The plyometric group performed eight weeks of selected plyometric training along with a normal badminton training program, and control group just performed normal badminton training. Cortisol blood sample, DHEA and DHEA/C ratio Levels were measured before and after twelve weeks. Both groups' data was analyzed using paired t-test and independent t-test statistical methods. Within-group comparison results showed statistically significant differences in cortisol levels (p=0.001), DHEA (p=0.008) and the ratio of DHEA/C (p=0.003) in the plyometric group. Also between-group variable comparisons showed significant differences in cortisol levels (p=0.026), DHEA (p=0.020) and the ratio of DHEA/C (p=0.004) after eight weeks of training. Findings showed that plyometric training reduces cortisol levels as a catabolic indicator and increases DHEA as an anabolic indicator.